Neon girls : a stripper's education in protest and power - Worley, Jennifer (HarperCollins, 2020)
A riveting true story of a young woman's days stripping in grunge-era San Francisco where a radical group of dancers banded together to unionize and run the club on their own terms. When graduate student Jenny Worley needed a fast way to earn more money, she found herself at the door of the Lusty Lady Theater in San Francisco, auditioning on a stage surrounded by mirrors, in platform heels, and not much else. So began Jenny's career as a stripper strutting the peepshow stage as her alter-ego "Polly" alongside women called Octopussy and Amnesia. But this wasn't your run-of-the-mill strip club--it was a peepshow populated by free-thinking women who talked feminist theory and swapped radical zines like lipstick. As management's discriminatory practices and the rise of hidden cameras stir up tension among the dancers, Jenny rallies them to demand change. Together, they organize the first strippers' union in the world and risk it all to take over the club and run it as a co-operative. Refusing to be treated as sex objects or disposable labor, they become instead the rulers of their kingdom. Jenny's elation over the Lusty Lady's revolution is tempered by her evolving understanding of the toll dancing has taken on her. When she finally hangs up her heels for good to finish her Ph.D., neither Jenny nor San Francisco are the same--but she and the cadre of wild, beautiful, brave women who run the Lusty Lady come out on top despite it all. A first-hand account as only an insider could tell it, Neon Girls paints a vivid picture of a bygone San Francisco and a fiercely feminist world within the sex industry, asking sharp questions about what keeps women from fighting for their rights, who benefits from capitalizing on desire, and how we can change entrenched systems of power.